PENGARUH ELECTRONIC SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Studi Pada Pelanggan Traveloka) - MOCHAMAD ALDI SYABANI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims is to determine the effect of Electronic Service Quality on Customer Loyaltythrough Customer Satisfaction as a mediating variable on Traveloka Customer. Thisexplanatory research explains the causal relationship between its variables through hypothesistesting. The sample of this research were selected using non-probability sampling techniquewith purposive sampling methods. This research examines responses from 251 respondents whohave used Traveloka more than twice and aged over 18 years. The research instrument testincluded outer model test, inner model test, hypothesis test, and sobel test. The direct hypothesistest using t-test while the indirect hypothesis test use the sobel test, and the data were analyzedusing Partial Least Square in Smart PLS 3.0 software. The result of this research shows that theelectronic service quality significantly affect the customer satisfaction, customer satisfactionsignificantly affect the customer loyalty, and electronic service quality significantly affect thecustomer loyalty. While for indirect influence of electronic service quality to customer loyaltythrough customer satisfaction showed significant result. This result means that customersatisfaction has a significant influence in bridging electronic service quality to customer loyalty.Keywords: Electronic Service Quality, Customer Satisfaction, Customer Loyalty,Traveloka